2014
DOI: 10.1007/s00167-014-3207-y
|View full text |Cite
|
Sign up to set email alerts
|

Shape and size of the medial patellofemoral ligament for the best surgical reconstruction: a human cadaveric study

Abstract: The MPFL is a distinct structure that goes from patella to femur with a sail-like shape; its patellar insertion, that mostly occur via an aponeurosis tissue with VMO and VI, is at the proximal third of the patella but it may extend in some cases to the medial third patella or to the quadriceps tendon, or very rarely to the distal third of the patella. In the femoral side, the MPFL is inserted in its own site, in most cases distinct both from epicondyle and adductor tubercle, located on average at a 9.5 mm dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
69
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 27 publications
2
69
0
4
Order By: Relevance
“…Previous studies have demonstrated that this structure is always injured after lateral patellar dislocation [10,12,13] thus, MPFL reconstruction is commonly performed to restore the patello-femoral stability. However, many technical errors during MPFL reconstruction could overload and alter the patello-femoral joint [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that this structure is always injured after lateral patellar dislocation [10,12,13] thus, MPFL reconstruction is commonly performed to restore the patello-femoral stability. However, many technical errors during MPFL reconstruction could overload and alter the patello-femoral joint [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The anatomy of the MPFL has been described in recent studies [2,11,24], and surgical insertion points have been defined [26]. Different surgical techniques for MPFL reconstruction exist, yet they all aim for anatomic insertion points [6,15,18].…”
Section: Introductionmentioning
confidence: 99%
“…29 Its insertion on the patella is broad, attaching along the proximal twothirds in a fan-shaped manner. 29,36 Kang et al 37 described 2 functional bundles of the MPFL. Use of a 2-limb graft technique, as we describe, as opposed to singleegraft limb patellar insertion allows for more accurate re-creation of these bundles and insertion on the MPFL.…”
Section: Discussionmentioning
confidence: 99%